Study of the transient combustion of highly densified biomass briquette (Bio-coke) in an air flow. (15th January 2017) - Yan, Hui; Fujita, Osamu
Highlights: Characteristics of transient combustion behavior of Bio-coke (newly developed highly densified biomass briquette fuel[4, 7] ) in end-face combustion system are shown. Mechanisms controlling transient combustion characteristics of the Bio-coke have been presented based on one dimensional numerical calculation in comparison with experimental results. The effects of volatile and moisture contents on transient combustion behavior are presented. The results of this study contribute for getting a better understanding of the combustion characteristics of this newly-developed biomass fuel and the design of a combustion furnace specialized for the Bio-coke. Abstract: End-face combustion experiments were conducted on cylindrical bio-coke (BIC), i.e., a highly densified biomass briquette, to investigate whether quasi-one-dimensional steady combustion can be attained in 400-K air flow, as measured by a steady regression rate. In the experiment, it was found that the average regression rate in the first 0.01 m of BIC was relatively small after ignition, whereas after the first 0.01 m, the average regression rate became almost steady and much larger than that in the first 0.01 m. This suggests that before the steady regression period is reached, a non-negligible unstable regression rate phase exists. To investigate this transient combustion phase, one-dimensional numerical calculations were conducted, and the time-dependent regression rate and temperature distribution were computed. The mechanisms controlling transient combustion and the effects of volatile and moisture contents on transient combustion behavior were examined. The results show that a transient combustion period exists before steady combustion is achieved. This transient combustion period decreases as volatile content increases, and moisture content has a similar effect on transient combustion as volatile content. The phenomenon can be explained by the different final steady temperature distribution and evolution rate from the initial temperature distribution to the final steady temperature distribution.